TRAUMA HEALING, SCREENING PENYAKIT TIDAK MENULAR, PEMBERIAN SEMBAKO DAN AIR BERSIH BAGI KORBAN BENCANA ALAM BANJIR BANDANG DESA CINTA MANIK KECAMATAN KARANG TENGAH KABUPATEN GARUT - Engkus Kusnadi; Angga Dipa Nagara; Hasbi Taobah Ramdani; Zahara Farhan; Novie Melliasany (Jurnal Pengabdian Masyarakat DEDIKASI, 2021)
Indonesia is a disaster laboratory with 13 types of disasters in it. The history of disaster events shows that there has been an increase in disasters from time to time. The increasing vulnerability factor and still limited capacity also cause disaster risk to increase in the future. Based on the above background, universities must uphold the Tridharma of Higher Education, so that the Community Service Program is held. This service was carried out in Cintamanik Village, Karang Tengah District, Garut Regency. This service is a collaboration between lecturers and students. In Garut Regency there was a flash flood on November 28, 2021 which resulted in physical and building damage in two villages in Karang Tengah sub-district, namely Cinta and Cinta Manik villages. The implementation method used is, indoor games for children, PTM examination for the elderly, and the provision of clean water. This activity will be held on December 23, 2021 in Cinta Manik Village, Karang Tengah District, Garut Regency. The target for this community service is 20 (twenty) children and 100 (one hundred) elderly residents in Cinta Manik Village. The main purpose of PTM activities is to increase community participation in the prevention and early detection of non-communicable disease risk factors (PTM). From this community service activity, clean water infrastructure is needed, trauma healing for children and examination of non-communicable diseases for the elderly